Making Roads Safer : Learning from the World Bank's Experience - Independent Evaluation Group (World Bank, Washington, DC, 2015)
Every year, nearly 1.3 million people worldwide are killed in road crashes, which have become the leading cause of death among people between the ages of fifteen and twenty-nine. More than 90 percent of the world s road fatalities occur in developing countries, and half of the accident victims are pedestrians, cyclists, and motorcyclists. Road accidents disproportionately affect the poor, making road safety an economic development issue. Many crash victims are of working age, and their death or serious injury too frequently leaves their dependents destitute. Governments in poorer countries have assumed they cannot act to reduce death rates until they are wealthier. However, many of today s road safety measures can be implemented relatively inexpensively to reduce death rates, if managed correctly. The United Nations (UN) invited the World Health Organization (WHO) to coordinate a drive to improve road safety globally. It also proclaimed a decade of action for road safety (2011 2020) to stabilize and then reduce the level of traffic fatalities and serious injuries around the world. More than 100 countries as well as multilateral development banks, including the World Bank, support the interventions. The Independent Evaluation Group (IEG) is aware of the rapidly worsening road safety situation in the developing world and efforts by the Bank's transport sector to encourage the use of best practices in road projects. This study, a pioneering learning product created by IEG in cooperation with transport operational staff and the Bank s Global Road Safety Facility (GRSF), aims to provide useful knowledge to Bank operational staff involved with road safety, to support Bank and client countries in fine tuning their road safety strategies and practices, and to support the acceleration of the Bank s operational road safety agenda.